Urbanization levels and its association with prevalence of risk factors and Colorectal Cancer Incidence - Mostafa Enayatrad (Tehran University of Medical Sciences, 2021)
Background: Colorectal cancer is one of the most common cancers in the world. This study aimed to determine the relationship between risk factors and the incidence of colorectal cancer in Urbanization levels in Iran.